Aproximações e estudos da ficção narrativa nos games - Cardoso, Franciely Gonçalves (2014)
The theme of the dissertation unfolds in the study of fictional narratives in games and how they are created, as well as the impact on the imagination. The playfulness is understood as a human, historical and cultural event. The "play is part of human history and cultural construction and narratives are used by humans to express themselves and to understand the world. This research considers the studies of Aesthetics of Reception, the dynamic relationship among author, work and reader. Traditionally narratives are told through various art forms such as romance, music, theater, film, poetry, among others. However, a more recent medium provides new experiences for those who have contact with the stories of these narratives: the electronic games. We know what to expect from more traditional narratives, however, how does the experience of the interactor, concept by Janet Murray (2003), with an electronic game occur? This then highlights the general objective of this research. The view of the act of playing is compared to the act of reading, and considering this choice of metaphor the game would be a book. A discussion of the work is based on the comparative studies and considers aspects of ludology and narratology. The research focuses on the comparative method to establish relations among artistic procedures. Literature, film and games are evidenced by indirect documentation involving bibliographic studies. Art and technology are themes of reflection and analysis. Scholars like Couchot (2003) argue that the game consists of a technological cultural phenomenon that has gained more space in society. Researches show that many people of different ages, but especially young people, spend more time playing computer games or consoles than watching television. In addition to Murray and Couchot , this research also supports the theoretical assumptions of authors such as Umberto Eco (1994, 2005), who deals with the production, reception and communication, Candido (2007), about the fictional character, Bakhtin (2003), who studied questions about aesthetics of artistic creation, and also Huizinga (2012) who analyzed the game as an element of culture, among others. Another goal of this research is the study of the mask used by the interactor, a representation of the virtual self that sees oneself as the hero character or avatar. As a result of this search the game is presented as a new way of storytelling where the main character is the interactor